Online ‘chatting’ interviews: An acceptable method for qualitative data collection - Joko Gunawan; Colleen Marzilli; Yupin Aungsuroch (Belitung Nursing Journal, 2022)
Qualitative research methods allow researchers to understand the experiences of patients, nurses, and other healthcare professionals. Qualitative research also provides scientists with information about how decisions are made and the aspects of existing interventions. However, to get to obtain this important information, qualitative research requires holistic, rich, and nuanced data that can be analyzed to determine themes, categories, or emerging patterns. Generally, offline or in-person interviews, focus group discussions, and observations are three core approaches to data collection. However, geographical barriers, logistic challenges, and emergency conditions, such as the COVID-19 pandemic have necessitated the utilization of online interviews, including chatting as an alternative way of collecting data. This editorial aims to discuss the possibility of online chat interviews as an acceptable design in qualitative data collection.